Myxomatous degeneration of aortic valve causing severe aortic regurgitation. A rare case report - Rakesh Kumar Kodakkandla; Venkata Sreedatta Sarraju; Nagesh Ayalasomayajula (SAGE Open Medical Case Reports)
Myxomatous degeneration of a valve is a non-inflammatory degenerative process due to the disruption of the fibrous layer of the valve with mucopolysaccharide accumulation. It is mostly seen in the mitral valve but involvement in only aortic valve is rare. Here we present a case report of a 37-year-old man who came with shortness of breath for the past three months and was diagnosed with severe aortic regurgitation due to myxomatous aortic valve causing rupture of the non-coronary and right coronary cusp. After preoperative workup, he was taken for aortic valve replacement surgery. Intraoperative findings confirmed the rupture of right and non-coronary cusps from their annular attachment and the myxomatous nature of the aortic valve. Histopathological examination confirmed the myxomatous changes in the valve. The patient underwent aortic valve replacement with a 23 mm TTK Chitra valve and on follow-up, he is doing well. Although aortic valve regurgitation is a common disease, myxomatous degeneration of isolated aortic valve leading to aortic regurgitation is rare. This patient did not have any signs of connective tissue disorders like Marfan’s syndrome, Ehlers-Danlos, etc., but presented with myxomatous aortic valve throwing an insight into further research into this rare disease.